Benzotriazole derivatives palladium complex: Synthesis, characterization, antifungal and catalytic activity - Patiño Rivera, Julian; Galarza de Becerra, Esperanza; De la Vega Quintero, Gala Paulina; Vesga Hernández, Carolina; De la Parra Morales, Alvaro Francisco (Scientia et Technica, 2019)
Two new palladium benzotriazole complexes (7) and (8) was synthetized from [PdCl2(NCCH3)2] (6) and the benzotriazole derivatives 1,3-phenylenebis-((1H-benzotriazol-1-yl)methanone) (3) and 1,3-bis(1H-benzotriazol-1-yl-methyl)benzene (5). Its antifungal and Mizoroki-Heck catalytic preliminar activity was evaluated, finding that the palladium complexes are more effective than the ligands against Aspergillus niger and the turn over number (TON) for the complexes 7 and 8 was 221 and 219, which are under the average for similar complex reported on literature.